The demon's den - Dixon, Franklin W.; Frame, Paul 1913-. (New York Simon and Schuster, 1984)
The Hardy boys, vacationing in Vermont, offer to help the police locate a missing camper and find themselves involved with a doomsday cult, a deadly strain of bacteria, and possibly the devil.
Keywords: Mystery and detective stories